High concentration of urokinase-type plasminogen activator receptor in the serum of women with primary breast cancer - Thielemann, Anna; Baszczuk, Aleksandra; Kopczyński, Przemysław; Kopczyński, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study was to assess the concentration of urokinase-type plasminogen activator receptor (uPAR) in the serum of 103 women with breast cancer. Commonly recognized prognostic factors were taken into account, including age, histological grade of malignancy, stage of clinical advancement of the disease, status of local axillary lymph nodes and the size of the primary tumour. Material and methods: The concentration of uPAR was assessed using an enzyme-linked immunosorbent assay (R&D Systems). Results : The concentration of uPAR in women with breast cancer was found to be higher than in a control group and the difference was statistically significant. The concentration of uPAR was found to increase in line with increasing disease stage and this too was of statistical significance. Raised levels of uPAR were found in women with breast cancer both with and without metastases to the lymph nodes of the axilla. A positive relationship was also found between the concentration of the tested receptor and the size of the primary tumour. No significant relationship, however, was found between the concentration of uPAR and the histological grade of malignancy of the tumour. No statistically significant results were obtained regarding the menopausal status of the women, that is, whether they were pre- or post-menopausal. Conclusions : Concentration of uPAR in serum of women with breast cancer is positively correlated with the stage of advancement of the disease. Thus, the assessment of this parameter can be useful in the clinical evaluation of women with breast cancer.